Forensics and Fallibility: Comparing the Views of Lawyers and Jurors - Garrett, Brandon L. (2016)
Forensic evidence plays an increasingly prominent role in criminal practice, leading some to worry that depictions in popular media might make jurors over-reliant on forensics — a so-called CSI effect. There is little empirical evidence of such a CSI effect among jury-eligible laypersons; any such influence also depends upon a case proceeding to a trial. As the Supreme Court has put it: “criminal justice today is for the most part a system of pleas, not a system of trials.” However, a CSI effect could be more consequential if it affects how criminal lawyers assess forensic evidence when they negotiate pleas or decide what evidence to present at trial. In this Essay, we begin to examine how criminal defense lawyers and prosecutors assess forensics, and we compare their views to those expressed by lay jurors. Part I of this Essay surveys the literature on the role that evidence plays in the plea bargaining process. In Part II, we present the results of two surveys that examine views on fingerprint and DNA evidence. Our focus was on two types of forensics: DNA evidence and fingerprint evidence. The evidence we gathered suggests misperceptions of both the evidence and how jurors will view the evidence. We found defense lawyers, in particular, may be far more skeptical of forensic evidence than jurors; indeed, defense lawyers may be overly skeptical of even DNA evidence. Most remarkable, however, was the great weight that jury-eligible adults placed on fingerprint evidence, just as many of the lawyers surveyed would have predicted, and even when compared to the weight they placed on DNA evidence. These results suggest far more must be done to study what information and influences shape the weight both lawyers and jurors place on forensics. We conclude in Part III by outlining how these surveys can provide a useful starting place for further research and policy